ANALISIS ASUHAN KEPERAWATAN PADA LANJUT USIA DENGAN PENERAPAN RENDAM KAKI AIR HANGAT UNTUK MENURUNKAN TEKANAN DARAH TINGGI - HERLINA MALINDA; YECY ANGGRENY (Jurnal Ners, 2022)
Hypertension has been known as a non-communicable disease that often occurs in elderly from Tresna Werdha Social Institution. Symptoms include sleep disturbances, dizziness, blurred vision, fatigue, and heart palpitations until no symptomatic but blood pressure exceeding 140/90 mmHg. This study aimed to analyze nursing care for the elderly using warm water foot soak therapy to reduce blood pressure at the Nursing Home of Tresna Werdha correctly, precisely, and by professional nursing standards. The research used a control and intervention group consisting of two subjects. The data collection instrument was an observation sheet. The intervention time was 30 minutes in the morning and evening on three consecutive days. The results of the implementation of warm water foot soak therapy in the two groups showed a reduction of mean difference in systolic 8.3 mmHg and diastolic 3.7 mmHg for the intervention group. In contrast, the control group was 4.3 mmHg and diastolic 4.7 mmHg. So it can be concluded that the warm water foot soak therapy performed on the elderly effectively reduces systolic blood pressure. At the same time, administering antihypertensive drugs reduces diastolic blood pressure effectively. Therefore, a recommendation was given to the PSTW to consider the implementation of warm water foot soaks therapy in the future to lower the blood pressure of the elderly.